1977
DOI: 10.1677/joe.0.0730473
|View full text |Cite
|
Sign up to set email alerts
|

An Homologous Radioimmunoassay for Chicken Follicle-Stimulating Hormone: Observations on the Ovulatory Cycle

Abstract: A highly purified FSH preparation has been used to develop a specific homologous radioimmunoassay for chicken FSH which is sufficiently sensitive and precise to measure the hormone in small sample (10-100 microliter) of plasma. The assay was used to measure plasma FSH in the chicken and turkey. The FSH concentration was higher in sexually mature chickens than in juvenile birds and further elevated after castration or ovariectomy. In turkeys, it was lower in birds held on a short daily photoperiod than in birds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

1978
1978
2005
2005

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(21 citation statements)
references
References 0 publications
2
19
0
Order By: Relevance
“…Early studies [10,11] demonstrated that granulosa cell condition [12] provided direct evidence that the granulosa cells of the four largest follicles of laying hen are the primary source of inhibin in the chicken. Our findings that the plasma FSH peak occurred 12 h before ovulation are in agreement with the reports of Scanes et al [6], and in contrast to the report of Vanmonfort et al [7].…”
Section: Discussionsupporting
confidence: 93%
“…Early studies [10,11] demonstrated that granulosa cell condition [12] provided direct evidence that the granulosa cells of the four largest follicles of laying hen are the primary source of inhibin in the chicken. Our findings that the plasma FSH peak occurred 12 h before ovulation are in agreement with the reports of Scanes et al [6], and in contrast to the report of Vanmonfort et al [7].…”
Section: Discussionsupporting
confidence: 93%
“…This concept of release from inhibition is relevant because it has recently been established that all hen follicles within the cohort from which selection occurs (both whole follicles as well as the isolated granulosa layers from these follicles) express FSH-R mRNA (Woods and Johnson; unpublished data). Assuming similar levels of receptor translation and functional coupling to signaling pathways prior to the selection process, one would expect equal follicle exposure to circulating FSH [37], and thus the potential for multiple follicles to simultaneously begin FSH-promoted differentiation. Results presented previously and herein are consistent with MAP kinase/Erk activity serving as an effective inhibitor of premature granulosa cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…LH, FSH, prolactin, growth hormone and androgens were measured using the radioimmunoassay systems described by Follett et al (1972), Scanes et al (1977), Lea et al (1982), Harvey and Scanes (1977) and Williams and Sharp (1978), respectively. All samples for each hormone were measured at one time to avoid variation between assays.…”
Section: Methodsmentioning
confidence: 99%